Recent Advances in Translational Electromagnetic Energy Harvesting: A Review - Marco Valerio Perrozzi; Mirco Lo Monaco; Aurelio Somà (Energies)
Wireless Sensor Nodes (WSNs) are becoming increasingly popular in various industrial sectors due to their capability of real-time remote monitoring of assets. Powering these devices with vibrational energy harvesters (EHs) provides multiple benefits, such as minimal maintenance and ideally infinite lifespan. Among the vibrational harvesters, translational electromagnetic ones (TEMEHs) are a promising solution due to their simple and reliable architecture and their ability to harvest energy at low frequencies. However, a major challenge is achieving a high power density. In this paper, recent literature about this typology of harvesters is reviewed. Different techniques to tune the resonance frequencies to the fundamental frequencies of the ambient vibrations are analyzed, such as non-linearities and multi-DOF configurations. The harvesters are classified on the basis of the suspension type, highlighting advantages and disadvantages. A final comparison is carried out in terms of NPD and FoMv, two indexes that evaluate power density in relation to size and excitation amplitudes.